MAKNA SIMBOLIK PADA KESENIAN KUDA LUMPING PANGERAN KUDA PUTIH DI DESA PERKEBUNAN KANOPAN ULU KECAMATAN KUALUH HULU - Pradana, Agung Surya; Mustaqimmah, Nurul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Kuda Lumping is a traditional art form originating from Java, combining elements of dance, music, and drama while using woven attributes shaped like horses. This art contains symbolic meanings embedded in the attributes and movements. However, in the Kuda Lumping Pangeran Kuda Putih performance in Desa Perkebunan Kanopan Ulu, Kecamatan Kualuh Hulu, there have been changes in the procession and attributes used, including the removal of some attributes due to certain factors. This study aims to analyze the symbolic meanings found in the situation, social interaction, and interpretation of this art form. The research uses a descriptive qualitative method with Herbert Blumer’s symbolic interaction theory as the theoretical framework. Data were collected through observation, interviews, and documentation, with six purposively selected informants. Data validity was ensured through method and source triangulation. The results indicate that the symbolic situation meanings in the Kuda Lumping Pangeran Kuda Putih performance consist of physical objects, namely the attributes used in the performance, and social objects, such as mantras and movements performed. The meanings of social interaction products vary among the older generation, the youth, and the performers. Interpretation meanings include open actions, which are directly observable expressions of the artists, and hidden actions, which are not directly visible and not fully recognized by others. Keywords: Meaning, Symbolic, Art, Kuda Lumping